Analyses of carbohydrates of apolipoprotein E in WLDL and IDL plus LDL of rat serum - Güldür, T; Lee, YC (Scientific Technical Research Council Turkey, 2002)
Carbohydrate compositions of apolipoprotein E (apo E) isolated from rat serum very low density lipoproteins (VLDL) and intermediate density lipoproteins (IDL) + low density lipoproteins (LDL) were analyzed and compared. Rat serum VLDL and IDL+LDL were isolated by a discontinuous density gradient ultracentrifugation for 7.9x10(7) g.min. Following delipidization, apolipoproteins were subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis. Apo E polypeptides were eluted by diffusion in 100 mM PBS buffer (pH 7) containing 0.05% SDS. Sugars were derivatized with 1-phenyl-3-methyl-5-pyrazolone (PMP) and subjected to high performance liquid chromatography (HPLC) analysis. N-acetylneuraminic acids of apo E were derivatized with 4,5-methylenedioxy-1,2-phenylene-diamine dihydrochloride (DMB). Detection of the derivatives was performed with fluorometric HPLC analysis. Mannose, galactosamine, galactose, fucose and N-acetylneuraminic acid contents of apo E were similar in both VLDL and IDL+LDL, while glucosamine content was higher in IDL+LDL (P<0.01). The present data indicate that the carbohydrate composition of apo E varies according to the density of lipoprotein particles containing the apo E. This heterogeneity might result from organ-specific glycosylation in glycan chains of apo E due to the fact that the majority of peripheral tissues are capable of synthesizing apo E and that they may contribute up to 4096 of total apo E synthesis.
Keywords: lipoprotein; apolipoprotein E; carbohydrate sequence